Reflexões sobre o desencaixe na educação brasileira e o eventual impasse entre o docentrismo e o discentrismo - Bastos, Alexandre Marucci [UNESP]; Kerbauy, Maria Teresa Miceli [UNESP] (My University, 2014)
Undocked institutions widely dilate the scope of time-space distancing, since the separation between these elements is crucial for the extreme dynamism of modernity. This separation is the prime condition of the process of disembedding, in which the displacement of social relations of local contexts of interaction and its redesign through indefinite extensions of time and space are favored. Therefore, there are two types of dislocated mechanisms intrinsically involved in the development of social modern institutions: symbolic tokens and expert systems. These mechanisms depend on reliability. Within this context, this present paper sees the professional life cycle of the teacher in the perspective of the expert system. It also sees the work stability of public servants in the symbolic token perspective, more specifically public teachers in Brazil. This paper also attempts to propose some reflections on what a disembedding in Brazilian education would mean and on how an eventual impasse between teachercentrism and studentcentrism would affect this process if necessary or desired, from one would understand by modernity.

As instituições desencaixadas dilatam amplamente o escopo do distanciamento tempo-espaço, já que a separação entre tais elementos é crucial para o extremo dinamismo da modernidade; sendo a condição principal do processo de desencaixe, pelo qual se favorece o deslocamento das relações sociais de contextos locais de interação e sua reestruturação por meio de extensões indefinidas de tempo e espaço. Para tanto, há dois tipos de mecanismos de desencaixe intrinsecamente envolvidos no desenvolvimento das instituições sociais modernas: “fichas simbólicas” e “sistemas peritos”. Mecanismos estes que dependem de confiança. Nesse contexto, o presente trabalho coloca o Ciclo de Vida Profissional do Professor (CVPP) sob a perspectiva do sistema perito; e a estabilidade empregatícia do funcionalismo público na ótica da ficha simbólica – mais especificamente do professor da rede pública de ensino no Brasil. Na pretensão de propor algumas reflexões sobre o que seria um desencaixe na Educação Brasileira e no que um eventual impasse entre o “docentrismo” e o “discentrismo” afetaria esse processo se assim ele se fizer necessário ou desejado frente à modernidade.
Reflections on a disembedding in brazilian education and the eventual impasse between teachercentrism and studentcentrism
Keywords: Desencaixe; Sistema perito; Ficha simbólica; Ciclo de Vida Profissional do Professor - CVPP; Estabilidade empregatícia; Disembedding; Expert systems; Symbolic tokens; Professional Life Cycle of the Teacher; Work stability